PENGGUNAAN FLY ASH DAN VISCOCRETE PADA SELF COMPACTING CONCRETE - Handoko Sugiharto; Gideon Hadi Kusuma (Institute of Research and Community Outreach - Petra Christian University, 2001)
Self Compacting Concrete (SCC) gives a new solution in concrete technology, since SCC does not need vibrator for compacting. SCC has been used and developed abroad, however in Indonesia SCC is not used because there is no research about SCC yet. In this preliminary research, trial mix is performed to understand the characteristics and to calculate the materials composition to be used in SCC. From this trial mix, some variables are fixed and others are varied. This variable is examined further in the next trial mix. The workability is examined using slump cone method and flowability using L-shaped box. From this test, it is found out that to get the condition of self compactibility, viscocrete must be used. The binder (cement-fly ash) composition, is examined using 10:0, 8:2, 7:3, 6:4 cement to fly ash ratio, until the maximum of flowability and workability, which is 5:5. Viscocrete dose 1.5 % and 2 % did not show a significant difference for all binder composition. From the workability, flowability and strength point of view, binder composition 6:4 and viscocrete dose 1.5 % gives the optimal condition. Abstract in Bahasa Indonesia : Self Compacting Concrete (SCC) memberikan solusi baru dalam dunia teknologi beton karena tidak memerlukan vibrator untuk pemadatannya. SCC telah digunakan dan dikembangkan di luar negeri, tetapi di Indonesia belum begitu dikenal, dikarenakan belum adanya penelitian tentang SCC di Indonesia. Pada penelitian awal ini dilakukan trial mix untuk mengetahui karakteristik dan memperkirakan komposisi bahan yang dibutuhkan untuk SCC. Kemudian dari trial mix tersebut ditetapkan variabel-variabel berubah dan variabel-variabel tetap yang akan diuji pada trial mix selanjutnya. Pengujian workability dilakukan dengan alat slump cone sedangkan pengujian flowability dilakukan dengan alat L-shaped box. Dari hasil pengujian yang telah dilakukan, ternyata harus digunakan viscocrete untuk mendapatkan kondisi self compactibility. Untuk komposisi semen dengan bahan pengisi fly ash dilakukan dengan komposisi binder (semen : fly ash) 10:0, 8:2, 7:3, 6:4 dan sampai batas flowability dan workability yang dapat dikerjakan, yaitu 5:5. Penggunaan dosis viscocrete 1.5 % dan 2 % tidak menunjukkan perbedaan yang signifikan pada tiap komposisi binder. Dari segi workability, flowability dan kuat tekan beton, komposisi binder 6:4 dan dosis viscocrete 1.5 % merupakan kondisi yang optimal.